Chess Results, 1971-1974 : a Comprehensive Record with 966 Tournament Crosstables and 148 Match Scores, with Sources. - Di Felice, Gino, 1955- (McFarland & Company, Inc., Publishers, 2014)
This continuation of a series of comprehensive chronological reference works lists the results of men''s chess competitions all over the world--individual and team matches. The present volume covers 1971 through 1974. Entries record location and, when available, the group that sponsored the event. First and last names of players are included whenever possible and are standardized for easy reference. Compiled from contemporary sources such as newspapers, periodicals, tournament records and match books, this work contains 966 tournament cross tables and 148 match scores, and is indexed by events.